2013
DOI: 10.1128/jvi.00448-13
|View full text |Cite|
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Modulates Cellular Vimentin for Virus Survival

Abstract: Foot-and-mouth disease virus (FMDV), the causative agent of foot-and-mouth disease, is an Aphthovirus within the Picornaviridae family. During infection with FMDV, several host cell membrane rearrangements occur to form sites of viral replication. FMDV protein 2C is part of the replication complex and thought to have multiple roles during virus replication. To better understand the role of 2C in the process of virus replication, we have been using a yeast two-hybrid approach to identify host proteins that inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 57 publications
5
52
1
Order By: Relevance
“…Several previous studies have suggested that vimentin plays an important role in several virus infections [5158]. In this work, we found that inhibition of vimentin by IDPN diminished virus yield, implying that vimentin plays a role in virus replication.…”
Section: Discussionsupporting
confidence: 64%
“…Several previous studies have suggested that vimentin plays an important role in several virus infections [5158]. In this work, we found that inhibition of vimentin by IDPN diminished virus yield, implying that vimentin plays a role in virus replication.…”
Section: Discussionsupporting
confidence: 64%
“…Proinflammatory cytokines such as TNF-␣ can trigger its secretion, while IL-10 (Th2 cytokine) is known to block its secretion in a PKC-dependent manner (62). Vimentin is essential for the replication of foot-andmouth disease virus, and it has been deregulated during Toxoplasma infection (28,63). An early low abundance (ϳ0.58-fold at 12 h) followed by an augmentation of its abundance (ϳ1.74-fold at 24 h and ϳ2.2-fold at 48 h) and gene expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work that focused on cellular proteins that interact with FMDV nonstructural protein 2C, we determined that viral 2C was able to bind cellular Beclin1 to prevent autophagosomelysosome fusion, favoring virus survival (27). We also discovered that 2C binds with cellular vimentin, a protein that forms a cage-like structure around 2C early during infection but must later be resolved for virus replication to progress (13). Here, we report that FMDV nonstructural protein 3A binds to DCTN3, a subunit of the dynactin complex that acts as a cofactor for the microtubule-base motor dynein.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar approach, we previously reported that FMDV 2C was able to bind cellular Beclin1 and vimentin facilitating virus replication (13). Here, we report that FMDV nonstructural protein 3A binds to DCTN3 (dynactin 3), a subunit of the dynactin complex that acts as a cofactor for the microtubule-base motor dynein.…”
mentioning
confidence: 86%